Anthropocene poetics : deep time, sacrifice zones, and extinction - Farrier, David, 1979- (Posthumanities, 2019)
"Anthropocene Poetics looks at contemporary anglophone poetry from Anthropocene, Plantationocene, and Multispecies perspectives, and sets out a poetics for thinking about 'geologic intimacy, ' the deeply relational reality of 'sacrifice zones, ' and processes of kin-making in a time of extinction"--